TRASFORMASI PEMBELAJARAN DASAR MELALUI INTEGRASI TEKNOLOGI DIGITAL PADA ERA SOCIETY 5.0 - Wulandari, Putri; Fauziah, Mutiara; Yurisman, Naila; Ari Suriani; Salmaini Safitri Syam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the Society 5. 0 era, technological developments are undergoing rapid change, both in the fields of digital technology, artificial intelligence (AI), and the Internet of Things (loT), bringing various changes, particularly to learning in elementary schools. This article aims to examine the role of digital technology in the Society 5.0 era on learning in elementary schools. The method used in this article is a literature riview, reviewing several relevant journals on the role of digital technology in elementary school learning. The results of the study indicate that the use of technology such as interactive videos and e-books can increase student learning interest. Thus, the integration of digital technology plays a crucial and innovative role in supporting effective and interactive learning in the Society 5.0 era.